2014
DOI: 10.1016/j.jegh.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Work productivity among adults with varied Body Mass Index: Results from a Canadian population-based survey

Abstract: This study found that obesity is an independent risk factor for reduced work productivity. Both absenteeism and presenteeism were associated with obesity. However, being overweight was weakly associated with work productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
4
23
0
4
Order By: Relevance
“…Bustillo et al, reported on 56,971 respondents to the 2009–2010 Canadian Community Health Survey and found that obesity is marginally associated with absenteeism and presenteeism. 50 BMI has been found to be associated with a number of other medical conditions among workers including emotional exhaustion, 51 menopausal vasomotor symptoms, 52 and diabetes-related metabolic risk factors in workers in China. 53 With rising levels of obesity among workers, employers are evaluating the impact of increasing weight not only on health care costs, but occupational injuries, absenteeism, presenteeism and thus, prompting a focus on workplace interventions to address this public health issue.…”
Section: Problem Of Obesity In the Workplacementioning
confidence: 99%
“…Bustillo et al, reported on 56,971 respondents to the 2009–2010 Canadian Community Health Survey and found that obesity is marginally associated with absenteeism and presenteeism. 50 BMI has been found to be associated with a number of other medical conditions among workers including emotional exhaustion, 51 menopausal vasomotor symptoms, 52 and diabetes-related metabolic risk factors in workers in China. 53 With rising levels of obesity among workers, employers are evaluating the impact of increasing weight not only on health care costs, but occupational injuries, absenteeism, presenteeism and thus, prompting a focus on workplace interventions to address this public health issue.…”
Section: Problem Of Obesity In the Workplacementioning
confidence: 99%
“…The prevalence of obesity has been on the rise for over four decades and has more than doubled since 1980 . The obesity epidemic is a universal concern because of its detrimental impacts on quality of life, disability‐adjusted life years, and life expectancy . Obesity is associated with a wide array of comorbidities such as depression, sleep apnea, musculoskeletal illnesses, pulmonary dysfunction, cardiovascular and metabolic comorbidities, cancers, impaired reproductive function, and others .…”
Section: Introductionmentioning
confidence: 99%
“… 25 Finally, international research has consistently found an association between obesity and impairments in work productivity measures, with increasing BMI linked to greater absenteeism and presenteeism. 7 , 26 29 …”
Section: Introductionmentioning
confidence: 99%